Pesan Dakwah Melalui Telegram: (Studi Pada Channel Syiar Tauhid Aceh) - Sy. Mazidah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This research was conducted to know the form of communication Da'wah that was built by the management of Da'wah Group on Channel Syiar Tauhid ACEH in the message of Da'wah messages, Da'wah material that is more often raised to the Channel Syiar Telegram Da'wah Group Tauhid Aceh to not be left behind in the message of Da'wah and the constraints faced during the process of delivering Da'wah messages through telegram on the channel Syiar Tauhid ACEH. Qualitative approaches and field research methods (Reseasch files) and library research. Data collection techniques in research are conducted with interviews, observations and documentation. Results of the research that the form of communication Da'wah that was built by the channel manager Da'wah on the channel Syiar Tauhid ACEH in the delivery of Da'wah messages consisting of question and answer in this respect the party Channel of Da'wah Aceh Syiar Tauhid A variety of Da'wah message materials both related to the message of Aqidah, as well as the message of Sharia and Ahklak. God. The obstacles faced during the process of delivering Da'wah messages through telegram on Channel Syiar Tauhid ACEH Competence Less and lack of the number of employees. The lack of the number of admins become the main constraint in delivering the messages of Da'wah by the Da'wah Channel Syiar Tauhid Aceh.